2004
DOI: 10.1242/jcs.00857
|View full text |Cite
|
Sign up to set email alerts
|

Lamellipodium extension and cadherin adhesion: two cell responses to cadherin activation relying on distinct signalling pathways

Abstract: Cell adhesion molecules of the cadherin family contribute to the regulation of cell shape and fate by mediating strong intercellular adhesion through Ca2+-dependent interaction of their ectodomain and association of their cytoplasmic tail to actin. However, the mechanisms co-ordinating cadherinmediated adhesion with the reorganization of the actin cytoskeleton remain elusive. Here, the formation of de novo contacts was dissected by spreading cells on a highly active N-cadherin homophilic ligand. Cells responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
110
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 54 publications
(57 reference statements)
21
110
2
4
Order By: Relevance
“…On Ecad-Fc-functionalized glass, cells were very flat and round, with large focal adhesion-like cadherin plaques at the end of thick radial F-actin bundles around the periphery ( Fig. 1E), similar to observations in previous studies (34)(35)(36)(37). These prominent F-actin and E-cadherin structures were very different from the organization of these proteins in cells adhered to Ecad-Fc PA gels.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On Ecad-Fc-functionalized glass, cells were very flat and round, with large focal adhesion-like cadherin plaques at the end of thick radial F-actin bundles around the periphery ( Fig. 1E), similar to observations in previous studies (34)(35)(36)(37). These prominent F-actin and E-cadherin structures were very different from the organization of these proteins in cells adhered to Ecad-Fc PA gels.…”
Section: Resultssupporting
confidence: 88%
“…The elastic moduli of the two gel formulations used in this study were verified by atomic force microscopy (AFM): 10%T, 1%C, 27.5-31.8 kPa (median: 29.07 kPa) and 10%T, 2.5% C, 52.6-67.2 kPa (median: 57.34 kPa) (Table S1). We also prepared glass coverslips (with an elastic modulus of ∼100 GPa) coated with Ecad-Fc, which have been used in most other studies (34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…Subcellular fractionation, GST-pull down, immunoprecipitation and western blot Cells were subjected to sub-cellular fractionation between membrane-containing pellet and cytosol-containing supernatant as detailed in (Gavard et al, 2004). Rac activation was monitored by GST pull-downs, using the GST-PAK-CRIB (Cdc42/Rac Interacting Binding domain) bound to glutathione slurry resin (GE Healthcare, Saclay, France), as described in (Gavard and Gutkind, 2006).…”
Section: Ve-cadherin Internalization Assay and Immunofluorescencementioning
confidence: 99%
“…It has been demonstrated that PI3K plays an essential role in the epidermal growth factor (EGF)-induced membrane protrusion by regulating not only Akt (Higuchi et al, 2001;Nishita et al, 2004;Hafizi et al, 2005) but also Rac and Ral GTPases (Tian et al, 2002;Gavard et al, 2004;Nishita et al, 2004;Takaya et al, 2004). However, the mechanism by which Akt regulates the cytoskeletal remodeling and the relationship to Ral and Rac has been still remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…PDK1 phosphorylates Akt at Thr 308 , which causes a charge-induced conformational change, allowing Akt for substrate binding and an increased rate of catalysis. Akt is further activated by the phosphorylation of Ser 473 , which can be catalyzed by various kinases, including PDK2, DNA-PK, mammalian target of rapamysin, rictor complex, integrin linked kinase, and protein kinase C␤II (Feng et al, 2004;Kawakami et al, 2004;Fayard et al, 2005;Sarbassov et al, 2005 It has been demonstrated that PI3K plays an essential role in the epidermal growth factor (EGF)-induced membrane protrusion by regulating not only Akt (Higuchi et al, 2001;Nishita et al, 2004;Hafizi et al, 2005) but also Rac and Ral GTPases (Tian et al, 2002;Gavard et al, 2004;Nishita et al, 2004;Takaya et al, 2004). However, the mechanism by which Akt regulates the cytoskeletal remodeling and the relationship to Ral and Rac has been still remains elusive.…”
mentioning
confidence: 99%